The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1532-5415.1998.tb03799.x
|View full text |Cite
|
Sign up to set email alerts
|

Home Environmental Hazards and the Risk of Fall Injury Events Among Community‐Dwelling Older Persons

Abstract: Current fall-prevention strategies of finding and changing all environmental hazards in all community-dwelling older persons' homes may have less potential effect than previously thought. The usefulness of grab bars, however, appears to warrant further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
3
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 30 publications
2
87
3
3
Order By: Relevance
“…Indeed, in contrast to the wealth of information available on personal characteristics and capacity, relatively little is known about the role of the environment in the day-to-day functioning of older persons, '4 and what little is known is limited largely to falls. [15][16][17][18] As a first step in elucidating the relationship between the environment and ADL functioning, we set out, in the current study, to describe the basic epidemiology of potential hazards in the homes of older persons. Our specific aims were to estimate the population-based prevalence of environmental hazards and to determine whether the prevalence of these hazards differs by housing type or by level ofADL disability.…”
mentioning
confidence: 99%
“…Indeed, in contrast to the wealth of information available on personal characteristics and capacity, relatively little is known about the role of the environment in the day-to-day functioning of older persons, '4 and what little is known is limited largely to falls. [15][16][17][18] As a first step in elucidating the relationship between the environment and ADL functioning, we set out, in the current study, to describe the basic epidemiology of potential hazards in the homes of older persons. Our specific aims were to estimate the population-based prevalence of environmental hazards and to determine whether the prevalence of these hazards differs by housing type or by level ofADL disability.…”
mentioning
confidence: 99%
“…Fear of falling has frequently been referred to in the literature as a significant barrier to full independence in the aged (Vellas, Wayne, Romero et al 1997;Lachman, Howland, Tennstedt et al 1998;Mclean & Lord 1996). The installation of grab rails has been cited as an effective method of not only preventing a fall but also reducing fear of falling (Sattin et al 1998;Mclean & Lord 1996). The personal attention of the visit and increased patient awareness could create a clouding effect with the perceived worthiness of modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of home modifications in preventing falls has been questioned (Norton et al 1997;Sattin et al 1998, Hinman 1998Carter et al 1997), but the Fall STOP project found increased confidence and a reduced fear of falling. Fear of falling has frequently been referred to in the literature as a significant barrier to full independence in the aged (Vellas, Wayne, Romero et al 1997;Lachman, Howland, Tennstedt et al 1998;Mclean & Lord 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations